A Personal Constructivist Approach for Investigating the Patterns of Dependency of Adolescents with Autism Spectrum Disorder: Case Study of Two Families. Issue 1 (2nd January 2016) - Cridland, Elizabeth K.; Caputi, Peter; Walker, Beverly M.; Jones, Sandra C.; Magee, Christopher A.
Abstract : This research investigated the utility and practicality of dependency grids for capturing and presenting the dependency distribution patterns of three adolescents with autism spectrum disorder. The investigation also involved family members to explore their level of awareness of the adolescents' dependency preferences. The grids were analyzed using a range of measures, including the uncertainty index and partial order scalogram analysis. Findings indicate the adolescents had various ways of dispersing their dependencies among their resources and differed in the types of support most used. Additionally, family members differed in their awareness of the adolescents' preferences. The benefits and drawbacks of the adolescents' dependency distribution patterns are discussed, as well as implications of these patterns for family members. Ways in which dependency grids may be further used with this population in research and clinical contexts are also considered.